Manajemen Strategi Inovasi Produk dalam Mendukung Pertumbuhan UMKM: Observasi pada Usaha “3S Teh Cem” - Theysa Sahlani Pratiwi; Siti Rugayah; Mutiara Praptasari (CV Edujavare Publishing, 2024)
An MSME that is developing will always experience challenges that are not small and not easy; with the increasing number of people who want to open a business, the competition against other business actors will become tighter, and every MSME business actor will increasingly be faced with various challenges such as limited labor resources. And will continue to compete with larger businesses. Micro, small, and medium enterprises (MSMEs) such as